The Application of Extracellular Vesicles Mediated miRNAs in Osteoarthritis: Current Knowledge and Perspective - Shang X; Fang Y; Xin W; You H (Dove Medical Press, 2022)
Xiaobin Shang,1,* Yan Fang,2,* Wenqiang Xin,3 Hongbo You1 1Department of Orthopaedics, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 2Department of Anesthesiology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 3Department of Neurosurgery, Tianjin Medical University General Hospital, Tianjin, 352000, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongbo You, Email hongboyou2014@outlook.comAbstract: Osteoarthritis (OA) is a whole joint disease characterized by synovitis, cartilage destruction, and subchondral bone sclerosis and cyst. Despite decades' study, effective treatment is rare for this chronic disease. Extracellular vesicles (EVs), including exosomes, microvesicles, and apoptosis bodies, are nano-sized vesicles with a cargo containing biologically active agents, such as nucleic acids, lipids, and proteins. As a group of short non-coding RNAs, microRNAs (miRNAs) can be delivered by parental cells secreted EVs. Negatively regulate the target mRNAs at the posttranscriptional level and regulate gene expression in recipient cells without modifying gene sequence. Recently, most studies focused on the function of EVs mediated miRNAs in the pathophysiological process of OA. However, all kinds of EVs specific and OA specific factors might influence the administration of EVs-miRNAs, especially the precise quantitative management. As a result, the flourishing of current research about EVs in the laboratory might not promote the relevant clinical transformation in OA treatment. In this review, we reviewed the present application of EVs-miRNAs in the therapeutic of OA and further analyzed the potential factors that might influence its application. Further progress in the quantitative management of EVs-miRNAs would accelerate the clinical transformation of miRNAs enriched EVs in the OA field.Keywords: osteoarthritis, extracellular vesicles, microRNAs, quantitative management, clinical transformation